Expression and roles of sympathetic and sensory nerves in perivascular adipose tissue - Abu-Bakar, Hamidah (2016)
There is a call to elucidate the poorly understood link between perivascular adipose tissue (PVAT) and nervous systems controlling the vasculature. The principle aims of this study were to investigate the expression of sympathetic and sensory nerves in PVAT of rat mesenteric arteries, to characterize their role(s) in vascular tone and to investigate the interaction between these nervous systems and PVAT-derived vasoactive compounds.